2014
DOI: 10.1021/am500362k
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Dip Coating of Zwitterionic Sulfobetaine Polymers on Hydrophobic and Hydrophilic Surfaces

Abstract: Zwitterionic sulfobetaine polymers with a catechol chain end (DOPA-PSB) were applied to a variety of hydrophobic polymer sheets and fibers. In addition, a silica surface was tested as a representative hydrophilic substrate. The polymer-coated surfaces showed significantly lower fouling levels than uncoated controls. Because of the anti-polyelectrolyte nature of sulfobetaine zwitterionic polymers, the effect of salt concentration on the coating solutions and the quality of the polymer coating against fouling ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
110
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(112 citation statements)
references
References 42 publications
1
110
0
1
Order By: Relevance
“…Many reports in literature have shown that thiol and amine terminated functionalized polymers could covalently bond to the dopamine molecule, and several papers also specifically used the polydopamine layer for this bonding process [8,46,49]. Messersmith et al suggested a possible polymerisation mechanism for dopamine [22], which leads us to believe that at mildly alkaline pH the PLL-g-PEG ad-layer could be covalently grafted to the dopamine molecules of the polydopamine film through Michael or Schiff-base reactions.…”
Section: Qcm-d Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports in literature have shown that thiol and amine terminated functionalized polymers could covalently bond to the dopamine molecule, and several papers also specifically used the polydopamine layer for this bonding process [8,46,49]. Messersmith et al suggested a possible polymerisation mechanism for dopamine [22], which leads us to believe that at mildly alkaline pH the PLL-g-PEG ad-layer could be covalently grafted to the dopamine molecules of the polydopamine film through Michael or Schiff-base reactions.…”
Section: Qcm-d Analysismentioning
confidence: 99%
“…The polydopamine layer not only readily adheres to most surfaces, but also provides a surface which allows various secondary reactions to take place and could therefore more easily enable the functionalization of material surfaces [22]. The reactions the catechol group of dopamine undergoes with metals, thiols, and amines has led to many research groups favouring the inclusion of dopamine when treating these surfaces [8,22,[24][25][26]36]. While many DOPA-functionalised grafting-to methods have proved successful on the specific surfaces listed above, researchers have encountered fouling when trying the same approach for hydrophobic surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30] Sulfobetaine pendant groups have strong hydration capacity due to the ionic solvation. [31][32][33][34] The use of surface-initiated atom transfer radical polymerization (SI-ATRP) for the preparation of polymer brushes enables precise control of their architectural features, such as the grafting density, the thickness and the composition; therefore, the interfacial properties of polymer films can be tuned flexibly.…”
Section: Introductionmentioning
confidence: 99%
“…But also zwitterionic polymers, such as poly(sulfobetaine methacrylate) (PSBMA), have been found to provide non‐fouling properties. Polymers incorporating zwitterionic moieties, for example, phosphorylcholine and carboxybetaine are excellent candidates for the creation of antifouling surfaces due to their anionic and cationic terminal groups, which form a strong hydration layer as an effect of the solvation of the charged groups …”
Section: Introductionmentioning
confidence: 99%